ASSESSING ANALYTICS MATURITY LEVEL IN THE INDONESIAN TAX ADMINISTRATION: THE CASE OF COMPLIANCE RISK MANAGEMENT - Prastuti, Gitarani; Lasmin (Scientax, 2021)
Using Grossman (2018)’s Analytic Process Maturity Model (APMM) Framework, we examine the maturity level of advanced analytics development related to taxpayer compliance management in the Indonesian Tax Administration, Directorate General of Taxes (DGT). The framework helps to indicate room for improvement within revenue bodies to allow the organisation to become more analytics-driven in dealing with the COVID-19 crisis and in the future. The results suggest that the organisation has reached a maturity level of 4.43 and capable of applying from enterprise-wide data analytics. To establish an analytics-driven organisation, remedial works are required to upgrade the current maturity level. Revenue authorities that have similarities in the economic background, compliance structure, and maturity level could acquire valuable lessons from Indonesia’s experience that could be considered in the further development of advanced analytics within taxpayer compliance management.